2016
DOI: 10.2967/jnmt.116.181479
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Signature on 18F-FDG PET/CT, HER2 Status, and Survival in Gastric Adenocarcinomas

Abstract: The human epidermal growth factor 2 (HER2)-overexpressing (HER2-positive [HER21]) gastric (GC) and gastroesophageal junction adenocarcinomas (GEJC) are felt to represent a more aggressive form of disease, which may correlate to increased metabolic activity. Whether tumor SUV max measured by 18 F-FDG PET/CT could be a preoperative parameter used to predict HER2 status of GC/GEJC is unknown. Methods: Pathology reports of HER21 GC/GEJC biopsies and resections from 31 patients were reviewed and compared with HER2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 31 publications
3
10
0
Order By: Relevance
“…Specifically, while some studies have reported that the SUV max is significantly lower in HER2positive group than in the HER2-negative group [10], others have drawn the opposite conclusion [33]. Consistent with results reported by Celli et al [34], our data demonstrate that there is no significant difference in SUV max between HER2 + and HER2− groups, implying that this marker cannot be used to predict the HER2 expression status of GEJC on initial staging.…”
Section: Discussionsupporting
confidence: 80%
“…Specifically, while some studies have reported that the SUV max is significantly lower in HER2positive group than in the HER2-negative group [10], others have drawn the opposite conclusion [33]. Consistent with results reported by Celli et al [34], our data demonstrate that there is no significant difference in SUV max between HER2 + and HER2− groups, implying that this marker cannot be used to predict the HER2 expression status of GEJC on initial staging.…”
Section: Discussionsupporting
confidence: 80%
“…As positron emission tomography (PET) technology using 18F-fluoro-2-deoxyglucose (FDG) is a manifestation of glycolysis in vivo [16, 17], the SUVmax has been widely used as a surrogate marker for the prognosis of disease in numerous types of cancer, including gastric cancer [18]. To confirm the relationship between Snail and glucose metabolism, we further analyzed the correlation between the Snail IHC staining and the PET/CT SUVmax data from gastric cancer patients.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have explored the relations between SUVmax and GC outcomes. Celli et al showed that patients with a high SUVmax demonstrated a worse overall survival, and metabolic signature of 18 F-FDG PET/CT is a better predictor of biologic tumor aggressiveness than histologic signature 8. Also, SUVmax was significantly higher in the HER2-negative group than in the HER2-positive group 53.…”
Section: Discussionmentioning
confidence: 99%
“…Imaging with fluorine 18 ( 18 F) fluorodeoxyglucose (FDG) positron emission tomography (PET) is a well-established method for staging GC, because it allows detection of distant metastases and lymph nodes involved 7. Conventional PET imaging metrics such as maximum standardized uptake value (SUVmax) and total lesion glycolysis (TLG) have been reported to be valuable prognostic factors in patients with GC 8, 9. Recent studies showed that metabolically active tumor volume (MATV) is a prognostic factor in patients with GC 10.…”
Section: Introductionmentioning
confidence: 99%